Scrolls and self-perception, navigating the link between social networks and body dissatisfaction in preadolescents and adolescents: a systematic review - Digennaro, Simone; Tescione, Alessia (Frontiers in Education, 2024)
In recent years, the widespread adoption of social media has immersed users in content dominated by conventional beauty ideals and the relentless pursuit of perfection. This pervasive influence has significantly altered the perceptual landscape for young individuals, particularly pre-adolescents and adolescents, shaping their self-evaluations and contributing to distorted notions of beauty. The virtual realm, saturated with carefully curated and idealized images promoting unattainable beauty standards, has intensified concerns about body image. This study aims to comprehensively examine the intricate interplay between social media use and the body image of preadolescents and adolescents. Through a meticulous systematic review of 16 studies, a consistent consensus emerges, highlighting a noteworthy correlation between key variables such as the duration of social media usage, problematic engagement patterns, specific activities within these platforms, and heightened levels of body dissatisfaction.